Kosalānandamahākāvyam : pracīna Chattīsagaṛha ke itihāsa para durlabha Saṃskr̥ta-pāṇḍulipi para ādhārita = Kosalananda mahakavyam = based on the palm-leaf mss 1664 - Shukla, Hira Lal. (Dillī : Nyū Bhāratīya Buka Kôrporeśana, 2000)
Epic poetry on Chattīsagaṛha (India).
Mode of access: Internet.
In Sanskrit; introd. in English.
Keywords: Chhattīsgarh (India) -- Poetry